The Rewriting of Mythology (Remythology) and Decolonization in Eka Kurniawan’s Man Tiger - Annisa Widyawati Fathonah (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2020)
This article examines the rewriting of mythology (remythology) in Eka Kurniawan’s magic realism novel titled Man Tiger (2004). The discussion particularly explores how the remythology of the Indonesian myth of manusia harimau responses to historical references that are embedded in the narrative. I found that remythology in the novel is used to replicate people’s voice, and by using that voice, the Indonesian nation attempts to decolonize itself from colonization and to epitomize a resistance against postcolonial powers. The myths surrounding manusia harimau in the novel further provide references to Indonesia’s identity that is located between two separate identities, the indigenous and the colonial, which comprise resistance as well as resilience. By using various local mythical frameworks, Eka Kurniawan addresses the complexity of the Indonesian nation which constitutes an acknowledgement, and an interpretation, as well as a response to the past in order to form a resilient present.